What do we know about Fake News?: A bibliometic analysis (Encuentros, 2022)
Fake news is frequently disseminated on social media with significant implications for public opinion, a phenomenon that increases academic interest in studying it. This research proposes to summarize the body of literature developed around fake news through a bibliometric analysis. For this, 1213 documents on the subject are analyzed, extracted from Scopus. Indicators are constructed identifying the evolution of scientific production, the most important journals, authors and organizations, countries with the highest production, bibliographic coupling networks and terms of greatest occurrence. The results suggest that studies on fake news have increased since 2016, coinciding with Brexit and the US elections, and the identification of six clusters that can guide future research by recognizing scientific trends.
Keywords: Fake news, post-truth, bibliometrics, social networks.